METHOD DEVELOPMENT AND VALIDATION OF TOTAL FLAVONOIDS ASSAY IN TABLETS WITH NOOTROPIC ACTION - N. N. Krylov; E. V. Kompantseva (Разработка и регистрация лекарственных средств, 2019)
Results of development of differential spectrophotometry method for determination of the total flavonoids assay in tablets containing dry extracts of ginkgo biloba are presented. Total flavonoid assay in leaves of ginkgo biloba and grass meadowsweet is preliminary presented by LLC «Vitaukt-Prom». The assay method for the sum of flavonoids in the dry extracts from this raw material and tablets «Ginkgotropil-forte» is developed. Justification of limit of flavonoid content in tablets «Ginkgotropil-forte» is presented and the limit is not less than 6 mg, based on the average weight of the tablet. The proposed method was validated for specificity, linearity, precision and accuracy.